Reliability and validity of the Lithuanian version of headache-attributed lost time (HALT) index - I. Zagorskienė; E. Abelkis; R. Mameniškienė (Neurologijos seminarai)
Background. Headache-Attributed Lost Time (HALT) index is a tool recommended by WHO to determine the burden of headache to the patient and his everyday life. This instrument has not been validated in Lithuanian so far. Objective. To perform cross-cultural adaptation of the Lithuanian HALT version and to test its reliability and validity. Materials and methods. The questionnaire was culturally adapted for Lithuanian speaking population following the recommendations of International Society for Pharmacoeconomics and Outcomes Research. Psychometric properties of HALT were tested on adults complaining of headache of any kind. Internal consistency and test-retest reliability after 2 weeks were determined. Construct validity was assessed using Visual Analog Scale (VAS) for Pain and Lithuanian version of SF-36v2 questionnaire. Results. Lithuanian version of HALT index (HALT-LT) satisfying requirements of linguistic and cultural adaptation was prepared. HALT-LT demonstrated acceptable internal consistency and test-retest reliability. Correlations for all proposed constructs were significant. Conclusions. HALT-LT can be used as an instrument for adult patients in Lithuanian speaking population. This questionnaire can become a convenient tool in the daily practice of a physician, assessing the burden of a headache.